PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Indolia Sidareja) - Azizatul Laili (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
This study aims to analyze the effect of product quality, and price, on purchasing decisions. The research method used is a quantitative method. This research uses simple random sampling. The sample in this study amounted to 75 respondents. Data collection instruments using questionnaires. The dependent variable is the purchasing decision variable and the independent variable is the price, product quality, and the price of the purchasing decision of Indolia Banana Sale. From the research, it shows that the product quality significantly influences the purchasing decision of Indolia Banana Sale. This is proven by t arithmetic greater than t table (1.955> 1.665). And the price has a significant effect on the purchase decision of Indolia Banana Sale, This is evidenced by t arithmetic greater than t table (3,066> 1,665). While the results of the simultaneous test of product quality and price variables, have a significant effect of (f arithmetic 4.667> f table 2.333) on purchasing decisions. This shows that, the better the quality of the product and the price given, the better the decision to buy Indolia Banana Sale.